1987
DOI: 10.1055/s-2006-962654
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Aldose Reductase Activities by Kampo Medicines

Abstract: 131itional medicine "Flachimi-Gan" act as insulin-like substances and, consequently, the above natural drugs may partly reduce the elevation of serum insulin levels without affecting glucose levels in rats fed the high sugar diet. Furthermore, cinnamic acid and cinnamic aldehyde were isolated as anti-lipolytic substances from Cinnamomi cortex. It was reported that cinnamic acid and cinnamic aldehyde inhibited the VLDL synthesis from acetate in rat hepatocytes (14). Therefore, these finding suggested that the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…The group of Kampo formulations that are clinically used for DN and for which AR inhibitory activities in the rat lens have been reported [19] exhibited significant hAR inhibiting effects in the present in vitro study. Moreover, Chotosan and Yokukansan exhibited greater AR inhibitory activities than this group of Kampo formulations.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…The group of Kampo formulations that are clinically used for DN and for which AR inhibitory activities in the rat lens have been reported [19] exhibited significant hAR inhibiting effects in the present in vitro study. Moreover, Chotosan and Yokukansan exhibited greater AR inhibitory activities than this group of Kampo formulations.…”
Section: Resultsmentioning
confidence: 61%
“…Goshajinkigan, Sokeikakketuto, Keishikajutsubuto and Hachimijiogan are clinically used for the treatment of peripheral neuropathy and were used as controls because previous reports exist only for these four formulations [19]. Four Kampo formulations, namely, Chotosan, Shichimotsukokato, Yokukansan, Yokukansankachinpihange, which are used for cognitive disorders were also selected to determine their AR inhibitory activities in this study (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The administration of aldose reductase inhibitors to prevent the development of diabetic microangiopathy and basement membrane thickening had previously been shown in animal models [20,21] . Kampo medicine but not insulin is effective in this context [31,32] .…”
Section: Discussionmentioning
confidence: 96%
“…Experimental research on the single herb ingredients as well as the 10-herb formula has revealed the following physiological activities: Antioxidative actions [27,28] , vasodilation, mediated through NO production [29] , anticoagulatory effects [30] , aldose reductase inhibition [31,32] and improvement of glucose utilization in both in vitro and animal models [33][34][35] .…”
Section: Introductionmentioning
confidence: 99%